The role of social media: impact on broadcasting industry / Farah Hazween Amanah, Nurliyana Kamilah Khairul Anuar and Muhammad Azril Izuan Ramlan - Amanah, Farah Hazween; Khairul Anuar, Nurliyana Kamilah; Izuan Ramlan, Muhammad Azril (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Media is very important in our lives. Media is used for disseminating information, entertainment, communication, sharing and expressing opinion and ideas. Media acts as a tool where it is useful to communicate and interact or reach a large number of audiences. There are types of media such as printed media, broadcast media and new media which is social media. Social media has become a very important platform of broadcast media. The existence of social media gives an impact towards the broadcast and printed media especially traditional media which is television and radio. Social media has changed the broadcasting industry where the way information is delivered and received. Audiences shift from television and radio to social media. Thus, social media plays an important role in today’s broadcasting landscape in terms of engaging and interactive audience, global reach and viral content and trendsetting. Traditional broadcast media is one direction, where the information transmitted in one-way communication between television or radio towards larger audiences without returning feedback. Unlike social media, the information is transmitted in two-way directions between the broadcast media and their audiences where the audience feedback by likes, comments, shares direct messages and Live. Audiences or social media users can actively interact with the content and information they received, expressing their thoughts, opinions and emotions in real- time. The engagement and interactivity by social media transformed traditional broadcast media from one-way communication into an inclusive and participatory platform that allows both creators and audiences.